COMMUNITY UNDERSTANDING OF CORUPPTION OF CRIMINAL MEASURES (Study Case in Malang) - Tinuk Dwi Cahyani (Legal Standing : Jurnal Ilmu Hukum, 2020)
Currently we are concerned when witnessing the news about Operation CatchingHands (OTT) or the action of the regional head. As for the case in East Java alone,there were 13 regional heads affected by the KPT OTT. In 2018 yesterday the KPKconducted OTT, as many as 30 times OTT and 20 of them involved regional heads(Kompas, 2/28/2019). Regarding the Eradication of Corruption, Indonesia actually has had regulations since 1971, through Law Number 3 of 1971 concerning Eradication of Corruption. Subsequently in 1999, Law Number 31 of 1999 concerning the Eradication of Corruption Acts became the main rule regarding law enforcement in eradicating corruption in Indonesia, which was later revised through Law Number 20 of 2001 in several articles. Based on the background above, the formulation of the problem in this study is: What is the community's understanding of corruption especially in the city of Malang? The type of data used are primary data, secondary data and tertiary data. Primary data were obtained from interviews with people in Malang who were not legal experts. Whereas Secondary Data is obtained from various sources or legal materials such as Law Number 31 of 1999 Concerning Corruption and other Regulations relating to corruption. While tertiary material is obtained from various corruption cases that occur in the city of Malang. Data is processed based on qualitative analysis. Where the researcher uses secondary legal material sources, namely by examining the elements of criminal acts of corruption, especially in Law Number 31 of 1999 concerning Eradication of Corruption, is it in accordance with the applicable regulations. The process of analyzing the data first is to examine the results of interviews with the community in Malang, then analyzed using Law Number 31 of 1999 Concerning Eradication of Corruption, is it in accordance with the applicable regulations. the results of the study the authors get field data that illustrates that in fact there are already a lot of general public especially in the poor city of Lowokwaru  sub-district who understand about criminal acts of corruption, but about 16% of the people there are less understanding of corruption, they just know the meaning corruption without knowing how and what they have to do if that happens or they know even they fear their security is threatened when showing their active role against corruption.